Clarification of some api characteristics in relation to caribou (Rangifer tarandus) - Pruitt, Jr., William O. (Rangifer, 1990)
A total of 2177 comparisons of api hardness vs. density in northern Saskatchewan, southeastern Manitoba and northeastern Finland revealed no consistent correlation (r varied from +.70 to -.17). A total of 1395 comparisons of horizontal hardness of the top layer of api to vertical hardness of the same layer of api in southeastern Manitoba, northeastern Finland and far eastern middle Finland revealed no consistent correlation (r varied from +.99 to -.20). Therefore one cannot substitute density for hardness nor horizontal hardness of the top layer for vertical hardness of the top layer in the terms of the Värriö Snow Index.